Emotion and Playful Elements in Mobile Learning - Taharim, Nurwahida Faradila; Lokman, Anitawati Mohd; Isa, Wan Abdul Rahim Wan Mohd (International Conference on Next Generation Mobile Applications, Services and Technologies (Print), 2016)
Integrating learner's emotion using a playful approach is seen as one of the best mechanism to enhance learner's experience in mobile learning. Thus, the research strives to determine the emotional responses that is formed by playful elements in mobile learning applications. The Kansei Design Model was adopted in this research to assess the emotional responses of thirty subjects towards six evaluation specimens that were carefully selected. In the assessment procedure, a total of 12 emotional keywords were identified suitable to portray emotional dimension to the domain. The result revealed that the design of playful mobile learning applications could be represented through the joyful and pleasurable concept. A joyful design seems to have bright colours and fun. A pleasurable design seems to have colourful display and pictures. The result could be used as insights in designing future playful mobile learning applications, which embeds targeted emotional responses by users.